Arabization: Its Concept, Importance, Methods, and Term Crisis - Basil Faisal AL-Zuâ€™bi; Hashim Saleh Manna; Rijal Mahdi (Indonesian Journal of Arabic Studies, 2023)
Purpose: The research aims to clarify the concept of Arabization and its importance and methods, then discuss the crisis of the term circulating among scholars to indicate that from the ancient to the modern. Design/ methods/approach: The descriptive method is used in the research, starting with induction and a statistical survey of ancient and modern scientists' use of the term indicative of Arabization and its synonyms, then analysis, classification, justification, processing, and meandering to determine the importance of Arabization and its conditions after treatment, followed by discussion and formulation of the results. Findings: The researcher reached a set of results, the most important of which are: Arabization is a growth factor for the language, activating thought, and its purpose is to facilitate cross-pollination between nations in affecting and influencing vocabulary, and the term must be unified and resolved its crisis, especially when the nomenclature that denotes the Arabization process overlaps.Â Â